Impact evaluation report: Egypt’s Takaful Cash Transfer Program: Second round report - El-Enbaby, Hoda; Elsabbagh, Dalia; Gilligan, Daniel O.; Karachiwalla, Naureen; Koch, Bastien; Kurdi, Sikandra (International Food Policy Research Institute, 2022)
Egypt introduced the Takaful and Karama Program (TKP), a pair of targeted cash transfer schemes in 2015. In 2018, the International Food Policy Research Institute (IFPRI) completed the first round of impact evaluation of TKP, based on household survey data collected after the first 15 months of the program. In the period between the first-round evaluation and the data collection for this report in January 2022, Egypt faced an enormous economic shock in the COVID-19 pandemic with a complete loss of tourism, which before the crisis was responsible for 12% of GDP and 10% of employment (IMF, 2021). A follow-up evaluation was designed to assess whether impacts estimated from the first round have been sustained and whether longer duration of treatment has led to impacts on additional outcome variables. This follow-up impact evaluation was conducted using a regression discontinuity (RD) design similar to the first round but using a different sample of households much more tightly concentrated around the 4500 thresholds to address concerns about the smaller discontinuity. We find that households invested in assets, particularly productive assets and Takaful households reduced their debt burdens. There were no measurable impacts of the Takaful program on household consumption or poverty, which may be partially explained by changes in household demographics. We also find that Takaful improved school enrollment and attendance and contributed to household’s ability to cope with shocks.